Knowledge, attitudes and perceptions related to covid19 among Beninese military . - ATADOKPEDE, AGBOMENOU FÉLIX (My University, 2021)
The aim of this study was to assess the level of knowledge guiding attitudes, and to highlight the perceptions of Beninese military personnel towards COVID-19. This is a cross-sectional study conducted from May 18 to June 16, 2020 in the garrison of Cotonou through the administration of an anonymous questionnaire to 836 participants. To assess the level of knowledge, major and minor criterion were defined. The level of attitude was assessed in relation to specific questions on the use of the hand washing device; the frequency of hand washing and the wearing of a mask. Above 50%, the level of general knowledge was considered "good". Statistics were analyzed by Stata 15.1. The mean age was 34.49 years. The sex ratio was 08.1. Officers were the most represented (55.27%). Soldiers from the 1st Motorized Intervention Battalion participated most in this study. It was found that 12.61% had a good level of knowledge and about 95% reported having a satisfactory attitude towards the coronavirus. Majority of participants (87.62%) declared that the pandemic had a negative impact on their lives. The level of knowledge of military personnel about the coronavirus is considered low. Initiatives based on appropriate information sources should be developed to strengthen their attitudes
Keywords: Knowledge; attitudes; perception; coronavirus; military personnel; Benin